2019
DOI: 10.1002/mds.27775
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and clustering of prodromal parkinsonian features in GBA1 carriers

Abstract: Background Five to 25% of patients with PD carry glucocerebrosidase gene mutations, and 10% to 30% of glucocerebrosidase carriers will develop PD by age 80. Stratification of PD risk in glucocerebrosidase carriers provides an opportunity to target disease‐modifying therapies. Objective Cross‐sectional and longitudinal survey of prodromal PD signs among glucocerebrosidase carriers. Design Prospective assessment of 82 glucocerebrosidase mutation carriers and 35 controls over 4 to 5 years for prodromal clinical P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
(57 reference statements)
0
34
0
Order By: Relevance
“…Carriers of GD have a yet unexplained significantly increased (20-fold) risk for developing Parkinson disease (PD) and Lewy body dementia (LBD) [110][111][112]. A recent study in the United Kingdom revealed that 5-25% of patients with PD carry glucocerebrosidase gene mutations, and 10-30% of glucocerebrosidase carriers will develop PD by age 80 [113]. Of note, active GCase activity is also decreased, and corresponding glycosphingolipid substrate levels elevated, in the brain in PD without GBA1 mutations [114,115].…”
Section: Gaucher Disease a Lysosomal Storage Disordermentioning
confidence: 99%
“…Carriers of GD have a yet unexplained significantly increased (20-fold) risk for developing Parkinson disease (PD) and Lewy body dementia (LBD) [110][111][112]. A recent study in the United Kingdom revealed that 5-25% of patients with PD carry glucocerebrosidase gene mutations, and 10-30% of glucocerebrosidase carriers will develop PD by age 80 [113]. Of note, active GCase activity is also decreased, and corresponding glycosphingolipid substrate levels elevated, in the brain in PD without GBA1 mutations [114,115].…”
Section: Gaucher Disease a Lysosomal Storage Disordermentioning
confidence: 99%
“…The clinical presentation of GD can be divided into systemic, which are present in all forms of GD, and include hepatosplenomegaly, painful skeletal disorders and pancytopenia, and neurological manifestations, which are present in the more severe types of GD, GD-II and GD-III. Both GD patients and healthy heterozygous carriers are at increased risk for PD [10] and longterm follow-up showed worsening in motor and non-motor prodromal PD features [11]. GBA mutations are a common risk for PD and are present in 7-10% of PD patients worldwide.…”
Section: Parkinsonism Associated With Gba Mutationsmentioning
confidence: 99%
“…As in GBA, different mutations and variants confer different levels of risk for PD. For example, the G2019S mutation, which is common in Whites, confers a higher risk for PD than the common Asian variants, G2385R and R1628P [11,13]. These latter two variants are detected in around 5-10% of Asian PD patients [45].…”
Section: Lrrk2-associated Parkinsonism: Kinase Inhibitors Are a Promomentioning
confidence: 99%
“…From another point of view, GD doctors might be sued for omitted, retarded, incompleted or potentially misleading information on PD risk to those who are potential candidates for future neuroprotective drugs or who already need a symptomatic treatment for early symptoms and signs of PD. Some longitudinal studies on GBA1 variant carriers provide evidence of a progressive worsening of motor and non-motor prodromal PD features [ 24 , 25 ]. The identification of GBA1 variant carriers and the early identification of subjects, either with mono or biallelic GBA1 mutations, who will develop PD is crucial to address patients to future neuroprotective drugs or at least to symptomatic treatments.…”
Section: Introductionmentioning
confidence: 99%